Arts, Health Promotion, and Social Justice: Synergy in Motion - Corbin, J. Hope (2021)
In this final chapter, drawing from examples presented in the book, we theorize a way of understanding how art may increase synergy in the pursuit of health promotion goals by facilitating deeper engagement with one?s self and with others, as well as by supporting the process of making sense of context. We also argue that art can promote social justice by amplifying voice, leveraging power, and honoring multiple ways of knowing. We conclude by highlighting implications for the field of health promotion and suggest lines of further research to build theory.